Implementation of integrated stepped care for unhealthy alcohol use in HIV clinics. Issue 1 (December 2016) - Edelman, E.; Hansen, Nathan; Cutter, Christopher; Danton, Cheryl; Fiellin, Lynn; O'Connor, Patrick; Williams, Emily; Maisto, Stephen; Bryant, Kendall; Fiellin, David
Abstract Background Effective counseling and pharmacotherapy for unhealthy alcohol use are rarely provided in HIV treatment settings to patients. Our goal was to describe factors influencing implementation of a stepped care model to address unhealthy alcohol use in HIV clinics from the perspectives of social workers, psychologists and addiction psychiatrists. Methods We conducted two focus groups with Social Workers (n = 4), Psychologists (n = 2), and Addiction Psychiatrists (n = 4) involved in an ongoing randomized controlled trial evaluating the effectiveness of integrated stepped care for unhealthy alcohol use in HIV-infected patients at five Veterans Health Administration (VA) HIV clinics. Data collection and analyses were guided by the Consolidated Framework for Implementation Research (CFIR) domains, with a focus on the three domains which we considered to be most relevant:intervention characteristics (i.e. motivational interviewing, pharmacotherapy), theinner setting (i.e. HIV clinics), andcharacteristics of individuals (i.e. the providers). A multidisciplinary team used directed content analysis to identify major themes. Results From the providers' perspective, the major implementation themes that emerged by CFIR domain included: (1)Intervention characteristics : providers valued tools and processes for facilitating patient motivation for treatment of unhealthy alcohol use given their perceived lack of motivation, but expressed a desire for greater flexibility; (2)Inner setting : treating unhealthy alcohol use in HIV clinics was perceived by providers to be consistent with VA priorities; and (3)Characteristics of individuals: there was high self-efficacy to conduct the intervention, an expressed need for more consistent utilization to maintain skills, and consideration of alternative models for delivering the components of the intervention. Conclusions Use of the CFIR framework reveals that implementation of integrated stepped care for unhealthy alcohol use in HIV clinics is facilitated by tools to help providers enhance patient motivation or address unhealthy alcohol use among patients perceived to be unmotivated. Implementation may be facilitated by its consistency with organizational values and existing models of care and attention to optimizing provider self-efficacy and roles (i.e. approaches to treatment integration).